Observations on the efficiency of using different cashmere combs - Ansari-Renani, Hamid R. (2013)
The effect of using small or large cashmere combs on cashmere harvest, cashmere quality and combing time was studied on Raeini cashmere goats in nomadic goat breeding systems of the Iranian province of Kerman. Two groups of 20 goats of different ages were combed with either a large or a small comb, three times with intervals of 2 weeks in early spring when natural fiber shedding has started. Combed cashmere weight, duration of combing, fiber diameter, and down yield were measured. A sample of combed cashmere was analyzed using a Laserscan instrument. A general linear model including type of comb, stage of combing and age of goat was fitted to analyze the data. Small combs collect more cashmere (31.0 vs. 21.7 g, P < 0.01) than large combs without affecting down yield or down fiber diameter (P > 0.05) but combing time is higher (3.75 vs. 2.79 min, P < 0.01). In the first two combing sessions much more cashmere was obtained than in the last (28.1, 32.0 and 19.0 g, respectively, P < 0.01), but the weight of total combed cashmere was much less than typical shorn fleece weights. Combing can be justified only if a considerable price premium can be obtained from selling combed cashmere instead of selling shorn cashmere, or if the combed cashmere is used to add value on-farm. If this is the case, small combs with short rods are preferable since more cashmere can be collected without affecting its quality